2016
DOI: 10.1177/2153368716658768
|View full text |Cite
|
Sign up to set email alerts
|

Racial Discrimination and Pathways to Delinquency

Abstract: The current study draws on two cohorts of African American youths from the Project on Human Development in Chicago Neighborhoods, Longitudinal Cohort Study to examine whether perceived racial discrimination directly and indirectly affects juvenile delinquency. The analyses reveal that racial discrimination may foster offending by increasing (1) the likelihood that African American youths will drop out of school and (2) the degree to which they associate with delinquent peers. Evidence supporting the pathway be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Not only do these challenges cut across salient domains during the transition to adulthood, but they also intersect with one another such that challenges in one domain may beget challenges in another. For example, racial discrimination presents challenges for establishing a positive self-concept (Kogan et al 2015), educational pursuits (Cabrera et al 1999; Johnson et al 2014), labor market opportunities (Gaddis 2015), romantic relationships and parenthood (Doyle and Molix 2014), and steering clear of the criminal justice system (Burt, Simons, and Gibbons 2012; Hope et al 2015; Unnever, Cullen, and Barnes 2016). Similar intersections during the transition to adulthood have been noted between romantic relationships and education (Schmidt and Lockwood 2015), educational pursuits and criminal justice involvement (Kirk and Sampson 2013), criminal justice involvement and labor market opportunities (Pager 2003), and so on.…”
Section: The Transition To Adulthood Among African Americansmentioning
confidence: 99%
“…Not only do these challenges cut across salient domains during the transition to adulthood, but they also intersect with one another such that challenges in one domain may beget challenges in another. For example, racial discrimination presents challenges for establishing a positive self-concept (Kogan et al 2015), educational pursuits (Cabrera et al 1999; Johnson et al 2014), labor market opportunities (Gaddis 2015), romantic relationships and parenthood (Doyle and Molix 2014), and steering clear of the criminal justice system (Burt, Simons, and Gibbons 2012; Hope et al 2015; Unnever, Cullen, and Barnes 2016). Similar intersections during the transition to adulthood have been noted between romantic relationships and education (Schmidt and Lockwood 2015), educational pursuits and criminal justice involvement (Kirk and Sampson 2013), criminal justice involvement and labor market opportunities (Pager 2003), and so on.…”
Section: The Transition To Adulthood Among African Americansmentioning
confidence: 99%
“…This approach translates racial stratification to the situational level and highlights the criminogenic effects of discriminatory interactions (e.g., Burt, Simons, and Gibbons, ; Unnever and Gabbidon, ). Focusing on African Americans, more than a dozen recent studies evince that IRD increases the risk of offending, including self‐reported violence (Caldwell et al., ; Simons et al., ; Stewart and Simons, ), delinquency (Martin et al., ; Unnever, Cullen, and Barnes, ; Unnever et al., ), and crime (Burt, Simons, and Gibbons, ), as well as official reports of arrest (McCord and Ensminger, , ). Several different measures of IRD are used, but all ask respondents to report whether they have experienced one or more negative acts because, from their perspective, they are Black or African American .…”
Section: Interpersonal Racial Discrimination and Crimementioning
confidence: 99%
“…However, recent research has questioned the validity of the racial/ethnic invariance thesis (Steffensmeier et al, 2010; Wright et al, 2014). Scholars argue that this thesis discounts the possibility that each minority group—and other nonminority groups including females—will be uniquely exposed to and differentially give meaning to their experiences with their systemic and chronic subordination (Unnever et al, 2015). It also dismisses the likelihood that causes of minority youth misconduct arise from their unique lived experiences with their racial or ethnic subordination (Wright et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Unnever et al (2015) observe that every group grounds its experiences with its racial/ethnic subordination within dissimilar group-based historical experiences and varying systemic and situational contexts. This suggests (a) that groups may be differentially exposed to racial/ethnic discrimination and (b) that such groups may differ in the meanings that they attach to their experiences with racial/ethnic discrimination.…”
Section: Perceived Police Discriminationmentioning
confidence: 99%
See 1 more Smart Citation